The use of Spirulina platensis as tilapiaOreochromis niloticusdiet supplementation - Utomo, Nur Bambang Priyo; Rahmatia, Firsty; Setiawati, Mia (Jurnal Akuakultur Indonesia, 2012)
Spirulina is blue green algae that have high nutrient content like protein and vitamin so itcan beused as source ofsingle cell protein (SCP). This research was conductedto know minimum doses of Spirulina in different protein feed on growth performance of tilapia. Experimental diets devided by two different protein level (25% of protein and 28% of protein) and three levels supplementation of Spirulina 0% (25A), protein level 25% supplementedSpirulina 3% (25B), protein level 25% supplementedSpirulina 6% (25C), protein level 28% supplementedSpirulina 0% (28A), protein level 28% suplemented Spirulina 3% (28B), and protein level 28% supplementedSpirulina 6% (28C). Testeds feedwere tilapia with average initial weight 17,24±0,29 g and density five fish/aquarium. Tilapia rearedin aquarium sized 50×40×35 cm3 filledwith 30 cm waterand provided altrecirculation system. Fish were cultured for 40 days and fed at satiation with three times feeding frequency. All data analyzed statistically by one-way ANOVA.Result demonstrated that various dosesof Spirulina in different protein level of feed influencedspecific growth rate, feeding efficiency, protein deposition, and fat deposition. Fish were fed by feed containing Spirulina 3% in protein level 25% showed growth performance as same as fed of protein level 28%. Keywords: feed protein, Spirulina, growth performance, tilapia